Estimation of the neutral real interest rate for Costa Rica - Muñoz-Salas, Evelyn (2017)
A central bank that uses the interest rate as monetary policy instrument requires an estimation of the neutral real interest rate (NRIR) that allows it to define the monetary policy stance to achieve its inflation target. This paper estimates the NRIR from actual values of the Monetary Policy Rate (TPM) for Costa Rica for the first time. This rate was established by the Central Bank of Costa Rica as its instrument for monetary control on June 2011. On the basis of monthly data from 2002-2015 and combining estimates from several methodologies, we estimate the neutral real interest rate for Costa Rica to be around 1,4%.